Calcium and vitamin D status in women of childbearing age in the rabat-Salé Kenitra region, Morocco - Leftat, Loubna; Ibrahmi, Btihaj AL; Arabi, Fatine EL; Khal-Layoun, Soad; Bour, Abdellatif (Edelweiss Applied Science and Technology, 2025)
Vitamin D deficiency is a significant public health issue in Morocco, affecting a considerable portion of the population despite favorable climatic conditions and abundant sunlight. The objective of this study was to evaluate the prevalence of vitamin D and calcium deficiencies among women of childbearing age in the Rabat-Salé region. A cross-sectional study was conducted between 2009 and 2010, involving a sample of 432 women aged 20 to 49 years who were non-pregnant and residing in the Rabat-Salé region. The collected samples were analyzed for 25-hydroxyvitamin D (25-OHD) and calcium levels. The results revealed that 94% of women had a deficiency, with 59.7% experiencing severe deficiency and 35.07% having moderate deficiency. The median 25(OH)D level for the moderate group (12.52 µg/L) was higher than that of the severe group (7.20 µg/L). Additionally, more than 38.43% of women had hypocalcemia, with 16.86% suffering from severe hypocalcemia and 21.57% experiencing moderate hypocalcemia. These findings highlight the need for vitamin D supplementation and increased awareness of the importance of a diet rich in micronutrients, particularly among women in this region.